Doping marker layers for ex situ growth characterisation of HVPE gallium nitride. Issue 5 (19th January 2017) - Hofmann, Patrick; Leibiger, Gunnar; Krupinski, Martin; Habel, Frank; Mikolajick, Thomas
Abstract : Doped marker layers are established to determine the transition temperature from 3D- to step flow growth mode of gallium nitride. Abstract : With this work we investigate several different ways to create marker layers for the ex situ characterisation of hydride vapour phase epitaxial (HVPE) gallium nitride (GaN) growth. Significant variations of the charge carrier concentration of GaN crystals become visible as marker lines in cross section investigations using optical microscopy and secondary electron microscopy (SEM). Pulsed intentional silicon and germanium doping leads to a good brightness contrast in cross section SEM micrographs and optical microscopy images. They appear as a black contrast in SEM. Pulsed manganese doping results in bright contrast marker layers in SEM, which is a result of the variation of the charge carrier concentration in the opposite direction, with respect to the background impurity level of the material. Marker layers are employed to determine the temperature transition point between 3D- and step flow GaN growth mode for the used set of growth parameters. A trend for the development of the growth rate of the c -facet as a function of the temperature is observed.